2014
DOI: 10.5942/jawwa.2014.106.0062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling conservative contaminant effects on reservoir water quality

Abstract: The Wachusett Reservoir in central Massachusetts was modeled using the two‐dimensional CEQUAL‐W2 hydrodynamic and water quality model to simulate a conservative contaminant spill from a roadway and analyze contaminant behavior at the Cosgrove drinking water intake 12.5 km (7.8 mi) from the spill site. Modeled calendar years 2003–09 were developed using meteorology, bathymetry, inflow quantity and quality, and outflow quantity data. Scenarios investigated included the influence of season, spill density, additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…The error in terms of water level similar for all models (~10 cm), and is in the range of errors reported in the literature (e.g. Dai et al, 2013;Jeznach et al, 2014;Chen et al, 2016;Bueche et al, 2020). GLM had a constant water level from Jan to May 2018, corresponding to the maximum level defined by the hypsographic curve due to the spillway crest elevation.…”
Section: Water Storage 490supporting
confidence: 74%
See 2 more Smart Citations
“…The error in terms of water level similar for all models (~10 cm), and is in the range of errors reported in the literature (e.g. Dai et al, 2013;Jeznach et al, 2014;Chen et al, 2016;Bueche et al, 2020). GLM had a constant water level from Jan to May 2018, corresponding to the maximum level defined by the hypsographic curve due to the spillway crest elevation.…”
Section: Water Storage 490supporting
confidence: 74%
“…This information is important for management of reservoirs during spilling accidents (e.g. Jeznach et al, 2014), for GLM it is not possible to estimate time travel, 560 since inflows are directly placed at defined layers. Studies assessing the inflow pathways through modeling demonstrated a good agreement between simulations and observations, for example Marti et al (2011) and (Zamani et al, 2020) with 3D models and Jeznach et al (2014) with CE-QUAL-W2.…”
Section: Longitudinal Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the water balance, all models had errors of comparable magnitude: 1D, 2D and 3D models had errors in stored water volume of −4.4 %, −4.9 % and −3.7 %. The error in terms of water level was similar for all models (∼ 10 cm) and is in the range of errors reported in the literature (e.g., Dai et al, 2013;Jeznach et al, 2014;Chen et al, 2016;Bueche et al, 2020). GLM had a constant water level from January to May 2018, corresponding to the maximum level defined by the hypsographic curve due to the spillway crest elevation.…”
Section: Water Storagesupporting
confidence: 79%
“…The model has been used to simulate a combination of rivers, lakes, reservoirs, and estuaries around the world (Cole & Wells, 2008). The CE‐QUAL‐W2 model was a logical choice for the current study because of its extensive calibration, verification, and application in many previous studies of the Wachusett Reservoir (Jeznach et al, 2014; Devonis, 2011; Sojkowski, 2011; Stauber, 2009; Matthews, 2007; Buttrick, 2005; Joaquin, 2001; CDM, 1995).…”
Section: Model Developmentmentioning
confidence: 99%